PENYAKIT UDANG VANAME (Litopenaeus vannamei) DI TAMBAK PT TANJUNG BEJO, PAJARAKAN KABUPATEN PROBOLINGGO - Musyaffa Rafiqie (Samakia : Jurnal Ilmu Perikanan, 2014)
This study aims to determine the type of disease affecting shrimp vannamei (Litopenaeus vannamei) in shrimp farms PT Tanjung Bejo, Pajarakan, Probolinggo. Business development activities vanamie enlargement shrimp (Litopenaeus vannamei), in ponds attention to the existence of diseases caused by microbes of viruses, bacteria, fungi and protozoa. Microbes are outstanding and never strike at PT Tanjung shrimp farms PT Bejo, Pajarakan, Probolinggo is kind of vibriosis, Taura Syndrome Virus, and Whitespot Bacilusvirus. In order to know and anticipate its spread or (early warning) and the types of microbes commonly attacked in shrimp farms PT. Tanjung Bejo, Pajarakan, Probolinggo, required profound observations about the type and identification of microbes, during the enlargement activities udan vanamie (Litopenaeus vannamei) in ponds.